Plurality of Meanings Strategy in the Architecture outcomes "Study of infinite meaning at deconstruction" - Alshamari, Haitham A. A.; Hmoud, Saad M.; Mhaibes, Mohammed K. (Nahrain University College of Engineering Journal, 2017)
Regardless of the general attitude of the architectural (deconstruction) movement and philosophical dimensions, But what concerns us is obtaining everything wholesome and values, including service and prove its concepts and mechanisms for the production of architectural shapes, So the search cared extraction strategy plurality of meaning and use them in any product architect without belonging to deconstruction movement.The thrill, meditation, fun, fascination, exaggeration, confusion, giving the impression, innovation and all other effects of psychological and sensory generated Pulled outcomes meanings in the architectural field to lend integrated architecture and recipients at the same time, The deconstruction particularize so through several mechanisms of deep philosophical after can be employed in any product is the most important (difference and interfaces, displacement, attendance, impact, immediate and dealing with the temporal dimension, vaccination).Search found that because of this strategy, "the plurality meaning" inherent (with most of its mechanisms) as a need for basic architectural movements, but the other is almost inherent in every product architect looking for the generation of meaning.Find Research problem:The problem in research:First: those most contemporary architecture outcomes bearing adopts the meaning inconsistent as it does not have a system or strategy collects. (Some sort of over).Second: the presence of the fear and the county in dealing with the architectural movement task such as motion deconstruction is therefore a kind of compromising.Aims of the research:1. Illustrate the importance of authenticity and strategy multiplicity of meaning in architectural production base and collector system of meanings generated.2. The importance of positives to draw architectural movements Bank, and try to employ them in various outcomes and other local architecture.3. Definition of a strategy of multiple meaning gives strength analysis of different architectural projects.Research Hypothesis:- Based on the premise that the search deconstruction adopts a strategy of multiple meanings in the creation of architectural production.- To verify the deconstruction of the mechanics of different infinite meaning.